Lightning characterization and mapping using microwave interferometer system - Al-Shaikhli, Taha Raad Khaleel (2021)
A lightning flash starts with the very first process called electron avalanche followed by streamer and leader. A leader is suggested to radiate intense electromagnetic fields below medium frequency (MF) bands while streamers are suggested to radiate intense very high frequency (VHF) electromagnetic fields. On the other hand, simulation results suggested that electron avalanches radiate strong microwave electromagnetic fields at around 1GHz. In this thesis, a microwave interferometer system has been developed, fabricated, and deployed with the aim to evaluate the temporal and spatial (2D mapping) characteristics of electron avalanches development during narrow bipolar event (NBE) discharges. So far, nothing has been published about microwave interferometer system with the purpose to map lightning microwave radiation. As the streamer is preceded by electron avalanches, detecting microwave radiation before the onset of VHF radiation could be used as a method to prove that electron avalanches radiate strong microwave radiation. In order to establish a microwave interferometer system, three finite-length capacitive antennas with resonance frequency around 1 GHz, low noise amplifier (LNA) operating between 0.9 and 1.2 GHz, bandpass filter (BPF) operating between 0.95 and 1.05 GHz have been designed and fabricated. Microwave radiations associated with 98 NBEs have been recorded and analysed. Out of 98 NBEs, only 18 high amplitude and low noise NBEs were selected with 17 +NBEs and one -NBE. About 11 from 18 microwave radiations have been detected earlier than VHF and NBEs onset time with average lead time of 211.55±82.49 ns. This is a strong indication of electron avalanches detected around 200 ns before the streamer formation. Moreover, clear bipolar pulses with duration less than 50 μs have been observed during the initial stage (IS) of the main burst. It can be suggested that electron avalanches process behave impulsively before the propagating streamers formed. Furthermore, three NBEs with associated microwave radiations have been mapped where the azimuth and elevation angles can be determined. The maps proved that all three NBEs were the result of fast positive breakdown where the electron avalanches (microwave) propagated upward while the positive streamers propagated downward.